A Brief Introduction to Bernard Lonergan’s Economics as a Science (London Journal of Research In Management & Business, 2024)
Regarding current economic theory, which has been focused on modelling for decades; are models empirical? Science is normatively considered to be explanatory thought combining both classical and statistical methods, beyond description, which begins with the data of the actual activity, in this case, economic activity and not imagined models. Bernard Lonergans analysis is empirical in that it begins with the data of actual economic activity. (Lonergan, 1998) By distinguishing between what he called the surplus production circuit, which produces goods and services which are sold and used in further production, and the basic production circuit which delivers goods and services for consumption into the standard of living, and then by working out the functions, variables and relations between these two circuits, he established a heuristic standard model for both micro and macroeconomics. Schumpeter (1954, 1160) and others such as Kalecki (1990, 23) were aware of the two circuits and Schumpeter believed that a serious explanatory analysis of the two circuits was required but neither he nor any economists took up the task.
Keywords: Big Data; Decision Performance; Quality of Decisions; Efficiency of Decisions; Data Analysis; Tunisian Business